On Quasi Prime Fuzzy Submodules and Quasi Primary Fuzzy Submodules - Rabee Hadi (مجلة علوم ذي قار, 2019)
In this paper we give some results about fuzzy quasi prime submodules, also,we study the notion of quasi primary fuzzy submodules